Adeno-Associated Virus-Mediated Gene Transfer of Factor IX for Treatment of Hemophilia B by Gene Therapy - Herzog, Roland W.; High, Katherine A. (Thrombosis and Haemostasis, 1999)
Patients with severe hemophilia have circulating blood coagulation factor VIII (hemophilia A) or factor IX (hemophilia B) levels below 1% of normal due to a genetic defect in the respective X-linked gene. The resulting bleeding disorder is characterized by spontaneous joint bleeds or, in a more life-threatening situation, into critical closed spaces, such as the intracranial or retroperitoneal space. Current treatment for hemophilia is based on intravenous infusions of clotting factor concentrates. These can be episode-based in response to bleeds (which does not prevent ongoing tissue damage nor the risk of a life-threatening bleed) or prophylactic (an expensive and not always practical alternative). The goal of a gene-based therapy is to introduce a functional clotting factor gene into a patient in order to provide a continuous supply of factor levels above 1%.1,2 Clinical endpoints for the efficacy of potential gene therapy trials for hemophilia are, therefore, well-defined and unequivocal.The relatively small size of the factor IX coding sequence (1.4 kb) and the fact that a number of cell types other than hepatocytes (which normally synthesize factor IX) are capable of producing biologically-active factor IX have contributed to the development of hemophilia B into an important model for the treatment of genetic diseases by gene therapy. The factor IX gene can be incorporated into a variety of vector systems. Various target tissues can be chosen for gene transfer as long as the secreted factor IX reaches the circulation and tight regulation of transgene expression is not required.3 Possibly most important in research on gene therapy for coagulation factor deficiencies, and genetic disorders in general, is the availability of a large animal model with severe disease. In this case, it is the well-characterized hemophilia B dogs maintained at the University of North Carolina at Chapel Hill. The animals contain a point-mutation in the portion of the factor IX gene encoding the catalytic domain. This mutation results in an absence of circulating factor IX antigen and, consequently, severe hemophilia B that closely mimics the human disease.4Gene therapy strategies for hemophilia B have typically established a method of gene transfer, resulting in expression of factor IX in mice, and subsequently, attempted scale-up to the dog model. These investigations have established experiments in the hemophilic dog model as a critical step for the assessment of the efficacy of gene therapy protocols showing initial promise in mice. For example, reimplantation of primary myoblasts that had been transduced ex vivo with a retrovirus was successful in mice, but not in the canine model.5 Adenoviral gene transfer, characterized by varying success in mice, depending on the strain and dose used, has persistently resulted in high, but transient expression following intravenous infusion into dogs.6,7 Cellular immune responses and hepatotoxicity have limited the expression of factor IX from adenoviral vectors to just a few weeks. Repeat administration of the vector was complicated by the induction of neutralizing antibodies to viral particles in injected animals following the first administration. Retroviral gene transfer to hepatocytes was successful in long-term expression of factor IX in hemophilia B dogs but required a partial hepatectomy prior to infusion of the vector through the portal vein. The resulting expression levels were no higher than 0.1% of normal human factor IX levels.8